The role of economic, fiscal, and financial shocks in the evolution of public sector pension funding - Robert K. Triest; Bo Zhao (Federal Reserve Bank of Boston, 2013)
Many studies have documented the pervasive underfunding of public sector pension plans in the United States in recent years. The deterioration of the funded status of public pension plans coincided with severe fiscal crises that state and local governments experienced in the 2000s. This development has led to a suspicion that state and local governments have decreased employer pension contributions as a backdoor means of running fiscal deficits. In this paper, the authors investigate the extent to which this phenomenon has occurred. They estimate panel data regressions using the Boston College Center for Retirement Research's Public Plans Database, which provides data for 2001 through 2010. The authors find that contrary to popular belief, plan sponsors do not reduce their contributions in response to negative fiscal or economic shocks. In contrast, plan sponsors' contributions to their pension plans increase in response to growth in their unfunded liabilities. The authors document that the public pension underfunding crisis during the 2000s developed largely as a consequence of portfolio returns that fell short of expectations. Public pension plans' assets portfolios have a relatively high share of equities and other risky assets, leaving the plans' funded status vulnerable to asset price fluctuations. Although plan sponsors increased their contributions in response to the growth of unfunded liabilities, they did not do so by enough to fully counteract the effect of the subpar portfolio returns. This finding holds across the spectrum of plans ranked in terms of funded status in 2010.
Keywords: H75; H72; G11; 330